100% Response Rate to Galcanezumab in Patients With Episodic Migraine: A Post Hoc Analysis of the Results From Phase 3, Randomized, Double‐Blind, Placebo‐Controlled EVOLVE‐1 and EVOLVE‐2 Studies. Issue 9 (20th October 2018) - Rosen, Noah; Pearlman, Eric; Ruff, Dustin; Day, Kathleen; Jim Nagy, Abraham
Abstract : Objective: To characterize adult patients with episodic migraine who achieved 100% response to galcanezumab treatment. Background: Galcanezumab is a humanized monoclonal antibody that selectively binds to the calcitonin gene‐related peptide (CGRP) and has demonstrated efficacy in reducing migraine headache days (MHD) in patients with episodic and chronic migraine. Methods: A post hoc analysis of the proportion of patients with 100% response (100% reduction from baseline in monthly MHD) was calculated for each month from pooled data of 2 double‐blind, 6‐month galcanezumab studies in patients with episodic migraine (4 to 14 MHD and ≥2 migraine attacks per month at baseline). The patients were randomized (1:1:2) to monthly subcutaneous galcanezumab, 120 mg (after 240 mg initial loading dose) or 240 mg, or placebo. A generalized linear mixed model with effects for baseline MHD, treatment, month, and treatment‐by‐month interaction was used to estimate the mean monthly response rate. Results: The analysis included 1739 patients treated with galcanezumab, 120 mg (n = 436) or 240 mg (n = 428), or placebo (n = 875). The mean monthly 100% response rate on an average month in the 6‐month double‐blind phase was greater for galcanezumab 120 mg (13.5%) and 240 mg (14.3%) groups vs placebo (5.9%) with odds ratios of 2.5 (95% confidence interval [CI] 1.9, 3.2) and 2.6 (95% CI 2.0, 3.4), respectively ( P < .001). The rate of 100% monthly response increased at each month over the 6‐month double‐blind phase with higher rates for galcanezumab dose groups (9 to 21%) than placebo (2 to 10%) ( P < .02). Evaluation of 100% response by the number of months showed a greater proportion of galcanezumab‐treated patients in either dose group, compared to placebo, were able to achieve a 100% response ( P < .001 up to 3 months); however, though greater than placebo, few galcanezumab patients had ≥4 months of 100% response ( P < .02). The proportions of patients with 100% response were greatest in the last 3 months of the treatment. Considering the average number days between nonconsecutive MHD across the 6‐month period (not just during the times of 100% response), the duration of migraine headache‐free periods in the galcanezumab groups was 29 days for those with at least 1 month of 100% response and 55 days for those with at least 3 months of 100% response. This gap was approximately 6 to 11 times greater than the mean gap of 5 days observed at baseline. Conclusions: More than a third of the patients with episodic migraine treated with galcanezumab 120 mg or 240 mg achieved 100% response for at least 1 month. More patients had 100% monthly response in the last 3 months of the 6‐month double‐blind period. For those with 100% response for at least 1 month, the average time between nonconsecutive MHD for the entire treatment period was nearly 1 month and approached 2 months for patients with 3 or more months of 100% response.